ERGONOMICS ASSESSMENT OF WORKSTATION DESIGN IN AUTOMOTIVE INDUSTRY - A. P., Puvanasvaran; A. R. , Ismail; N., Jusoh; A. Z. , Ismail; M. H. , Abu Bakar; W. H. W. , Deraman (2010)
The purpose of this study is to demonstrate the ability to interpret the various aspects of ergonomics contributions and influences in the manufacturing industry. The application of knowledge and understanding of the ergonomics theories and techniques in the manufacturing industry also will be demonstrated in this study. Besides that, this report will be able us to appreciate the ergonomic role in manufacturing industry and everyday context by showing the ergonomics contribution towards employees’ health and safety in the workplace and tangible or intangible profitability of the company. Adequate posture, work height, normal and maximum working areas are determined for the intended user population. The procedure for determining the workstation dimensions and layout has been explained. The importance of building a mock-up of the designed workstation and its evaluation with representative subjects is emphasized. A case problem (Final Inspection workstation) is discussed to illustrate the workstation design procedure.